Updated Zeeman effect splitting coefficients for molecular oxygen in planetary applications. (February 2019) - Larsson, Richard; Lankhaar, Boy; Eriksson, Patrick
Highlights: We present a more accurate way to compute Zeeman effect for O2 . We show the effects of these updates on measurements from existing platform. The update makes retrieved magnetic field strength better agree with modeled strength. Abstract: We comment on a common practice to use pure Hund case (b) Zeeman parameters in planetary atmospheric radiative transfer applications involving molecular oxygen. A detailed theoretical formulation is presented for the Zeeman splitting coefficients of molecular oxygen in its ground vibronic state, taking also the relevant fine-structure interactions into account. The updated Zeeman parameters are compared to the simplified Hund case (b) approach used in earlier works. The biggest differences between the output of these formulations occur for states with low rotational energy, and the differences are greater for 16 O 18 O than for 16 O2 . To get the order of magnitude error introduced by the simplification of the splitting coefficient computations, we perform a limited case study of forward simulations for a few space-borne and ground-based instruments. Our analysis shows that using simplified Zeeman coefficients introduces errors in the forward modelled radiation varying from insignificant up to 10 K.